Assessing The Impact of ISO 9001:2015 Implementation on the Service Delivery of The National Irrigation Administration (NIA) Regional Office VIII - Pascua, Alejandrino B.; Mades, Karen C.; Basquez, Sarah Jane B.; Funes, Maria Tacianne L.; Malang, Bernandino P.; Malang, Jocelyn DS. (Future Science / FSH-PH Publications, 2024)
This study assesses the impact of ISO 9001:2015 implementation on service delivery and operational efficiency at the National Irriga-tion Administration (NIA) Regional Office VIII. A descriptive research design was employed, utilizing both quantitative and qualitative methods. Data were collected from 312 internal and external stakeholders through stratified sampling. Descriptive Statistics, and Analysis of Variance (ANOVA) evaluated operational efficiency and stakeholder satisfaction. Key findings show that 65% of respondents reported improvements in operational efficiency, particularly through standardized processes that streamlined workflows. However, 48% indicated that additional documentation requirements slowed down operations. In terms of service delivery, 35% of respondents observed greater consistency and reliability, while 31% experi-enced delays due to the time-consuming nature of compliance procedures. Despite these gains, challenges such as resource con-straints and resistance to change limited full adoption, particularly among senior management. The study highlights that while ISO 9001:2015 enhanced both op-erational efficiency and service delivery, the increased documentation burden and procedural complexity introduced operational slow-downs. These findings offer valuable insights into the dual impact of ISO 9001:2015 in public sector organizations, illustrating its potential for improving service delivery while underscoring the challenges of maintaining efficiency amid compliance demands.